Chronic mast cell leukemia: A novel leukemia-variant with distinct morphological and clinical features. Issue 1 (January 2015) - Valent, Peter; Sotlar, Karl; Sperr, Wolfgang R.; Reiter, Andreas; Arock, Michel; Horny, Hans-Peter
Highlights Mast cell leukemia (MCL) is a rare fatal form of a mast cell disease. Based on the presence of organ damage, MCL is classified into acute MCL and chronic MCL. The variant of MCL correlates with the prognosis and with the morphology of mast cells.